Safety and efficacy of daclizumab in relapsing-remitting multiple sclerosis: 3-year results from the SELECTED open-label extension study - Gold, Ralf; Radue, Ernst-Wilhelm; Giovannoni, Gavin; Selmaj, Krzysztof; Havrdova, Eva; Stefoski, Dusan; Sprenger, Till; Montalban, Xavier; Cohan, Stanley; Umans, Kimberly; Greenberg, Steven J; Ozen, Gulden; et al. (BMC neurology, 2016)
BACKGROUND: Daclizumab is a humanized monoclonal antibody against CD25 that modulates interleukin 2 signaling. The SELECT TRILOGY of clinical studies (SELECT/SELECTION/SELECTED) evaluated the safety and efficacy of daclizumab in patients with relapsing-remitting multiple sclerosis (RRMS). We report the long-term safety and efficacy of daclizumab 150 mg subcutaneous every 4 weeks in patients with RRMS in the SELECTED open-label extension study. METHODS: An interim intent-to-treat analysis of all enrolled patients was performed in January 2014 for this ongoing study. RESULTS: The SELECTED study enrolled 90% of patients who completed SELECTION. In the safety and efficacy analysis (N = 410), median treatment time in SELECTED was 25 months (range, <1-45). Adverse events (AEs) were reported in 76% of patients, serious AEs (SAEs) excluding MS relapse in 16%, and treatment discontinuation due to AEs including multiple sclerosis (MS) relapse in 12%. AEs were primarily of mild to moderate severity, and common AEs (≥10%), excluding MS relapse, were nasopharyngitis (12%) and upper respiratory tract infection (12%). Most commonly reported SAEs (in ≥3 patients), excluding MS relapses, were increased serum hepatic enzymes, pneumonia, ulcerative colitis, and urinary tract infection (<1% each). Incidences of AE groups of interest include cutaneous events (28%), cutaneous SAEs (2%), gastrointestinal SAEs (2%), hepatic SAEs, (1%) and malignancies (1%). The incidence of AEs, SAEs, and treatment-related study discontinuations did not increase over time and no deaths were reported. The adjusted annualized relapse rate (95% confidence interval (CI)) analyzed at 6-month intervals was 0.15 (0.10-0.22) for weeks 97-120 and 0.15 (0.10-0.21) for weeks 121-144. In year 3, the adjusted mean (95% CI) number of new/newly enlarging T2 hyperintense lesions was 1.26 (0.93-1.72) and the mean (median) annualized change in brain volume was -0.32% (-0.34%). CONCLUSIONS: The AE incidence did not increase with extension of therapy into year 3 in SELECTED; the safety profile was similar to that previously observed. The clinical efficacy of daclizumab was sustained over the 3 years comprising the SELECT TRILOGY, although potential selection bias cannot be excluded. TRIAL REGISTRATION: Clinicaltrials.gov NCT01051349; first registered January 15, 2010.
Keywords: infekce dýchací soustavy; dospělí; Alanine Transaminase; Nasopharyngitis; Aspartate Aminotransferases; Recurrence; Female; Pneumonia; alanintransaminasa; Safety; Interleukin-2 Receptor alpha Subunit; imunoglobulin G; pneumonie; Adult; výsledek terapie; ženské pohlaví; longitudinální studie; relabující-remitující roztroušená skleróza; Intention to Treat Analysis; lidé; Immunosuppressive Agents; recidiva; injekce subkutánní; Respiratory Tract Infections; Treatment Outcome; následné studie; mozek; Colitis, Ulcerative; Immunoglobulin G; kohortové studie; receptor interleukinu-2 - alfa-podjednotka; Middle Aged; Cohort Studies; Follow-Up Studies; aspartátaminotransferasy; Male; Urinary Tract Infections; Brain; Multiple Sclerosis, Relapsing-Remitting; Injections, Subcutaneous; ulcerózní kolitida; bezpečnost; infekce močového ústrojí; lidé středního věku; humanizované monoklonální protilátky; nazofaryngitida; Drug Eruptions; Antibodies, Monoclonal, Humanized; mužské pohlaví; analýza podle původního léčebného záměru; imunosupresiva; Longitudinal Studies; léková dermatitida; Humans